The Impact Of Information Technology and Supply Chain Management On Firm’s Operational Performance - Wahyudi Wahyudi (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the relationship between supply chain management and information technology on the operational performance of SMEs in Makassar. A quantitative approach was used in this research. A questionnaire survey was conducted to collect data from Makassar SMEs. Data was obtained directly from informants who were selected purposively, while respondents were selected randomly (Random Sampling). The selection of respondents was based on the assumption that the population was relatively homogeneous. The research results show that supply chain management and information technology have a positive and significant effect on the operational performance of SMEs in Makassar. Likewise, information technology has a positive and significant relationship to supply chain management.